Hodgkin lymphoma a comprehensive update on diagnostics and clinics - Engert, Andreas; Horning, Sandra J.; SpringerLink (Online service). (Heidelberg New York Springer-Verlag, 2011)
This book provides a well-illustrated, comprehensive, and up-to-date account of Hodgkin lymphoma. Epidemiology, pathogenesis, and the role of the microenvironment are examined in detail. The initial clinical evaluation and use of staging systems are fully discussed, and prognostic factors are carefully considered. The various treatment options for first-line and relapsed Hodgkin lymphoma are presented, including the newly available treatments for recurrent disease and the management required in special clinical circumstances. Given the very high cure rates and the young age of many patients, there is an increasing need to develop better individually tailored treatment strategies that will help to avoid both early and late side-effects of treatment. Such strategies receive due attention, and clear guidance is provided on the handling of Hodgkin survivors. This book will be of great value to hematologists, oncologists, and all others with an interest in Hodgkin lymphoma.
Epidemiology -- The role of viruses in the genesis of Hodgkin lymphoma -- Pathology and molecular pathology of Hodgkin lymphoma -- Microenvironment, cross-talk, and immune escape mechanisms -- Clinical evaluation -- Functional imaging -- Prognostic factors -- Principles of radiation techniques in Hodgkin lymphoma -- Principles of chemotherapy in Hodgkin lymphoma -- Treatment of early favorable Hodgkin lymphoma -- Treatment of early unfavorable Hodgkin lymphoma -- Treatment of advanced stage Hodgkin lymphoma -- Relapsed and refractory Hodgkin lymphoma -- Pediatric Hodgkin lymphoma -- Lymphocyte-predominant Hodgkin lymphoma -- The management of Hodgkin lymphoma during pregnancy -- The management of HIV- Hodgkin lymphoma -- The management of elderly patients with Hodgkin lymphoma -- Allogeneic transplantation for relapsed Hodgkin lymphoma -- New agents for patients with Hodgkin lymphoma -- Quality of life in Hodgkin lymphoma -- Second malignancy risk after treatment of Hodgkin lymphoma -- Cardiovascular and pulmonary late effects -- Gonadal dysfunction and fertility preservation in Hodgkin lymphoma patients -- What will we learn from genomics and proteomics in Hodgkin lymphoma? -- Personalized medicine in Hodgkin lymphoma?
Electronic reproduction.
Keywords: Hodgkin's disease; Electronic books